Tibial plateau fracture in a softball player - Anderson, D. M.; Dawson, C. A.; Cosgarea, A. J.; McFarland, E. G. (The Physician and Sportsmedicine, 2005)
Tibial plateau fractures typically are associated with high-energy mechanisms in young patients, as in the case of this 35-year-old softball player, and with low-energy trauma in the older population. A detailed history, careful physical examination, and plain radiographs constitute the essential initial study; MRI and CT are indicated to refine the diagnosis. Concomitant injuries are common, including ligament tears, meniscal damage, and other soft-tissue compromise. Less common but more devastating injuries include vascular disruption, nerve injury, and compartment syndrome. Injury severity determines whether treatment will be nonoperative or operative, but the goal is to restore the patient's normal function.